Table of Contents - Applied Informatics and Technolgoy, Journal of (Journal of Applied Informatics and Technology, 2018)
Research Articles in Computer Science and Information Technology - Syllabus Line Segmentation from Palm Leaf Manuscripts using Vector Neural Network - Comparison of Sampling Techniques for Imbalanced Data Classification - Drug Selection Support System for Targeted Cancer Therapy Based on Cell Signal Research Article in Information Science - A Bibliometric Analysis of Authorship and Collaboration Trend in Nature Nanotechnology - The Research Tools Used in the Articles of Annals of Library and Information Studies: An Analysis Research Articles in Digital Media - The Development of 3D Animation Cartoon to Promote the Integrity for Primary School Grade 4-6 Students